Efficiency of the EU Structural Support and its Effects on the Country’s Progress - Simanauskas, Leonas; Šidlauskas, Skirmantas (Ekonomika, 2007)
The article deals with the main method used by the European Union (hereinafter called the EU)to reduce the discrepancies in the economy of Lithuania - structural support for the country’s development and progress. The article analyses the economic, social, environmental, innovative and other indices of the economies of Lithuania and EU countries; the difference of particular indices of Lithuania and EU countries is assessed in marks. The progress of the Lithuanian economy in implementing the Lisbon strategy is evaluated according to eight groups of indices. The present study assesses the factors that correspond to the national implementation programme of the Lisbon strategy and the factors that influence the individual indices on the national progress.